2023
DOI: 10.21203/rs.3.rs-2243841/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of emergency extracorporeal shock wave lithotripsy in the treatment of ureteral stones: a meta-analysis

Abstract: Objective To compare the clinical efficiency and safety of emergency extracorporeal shock wave lithotripsy (eESWL) and delayed extracorporeal shock wave lithotripsy (dESWL) in the treatment of ureteral stones. Methods Cochrane Library, PubMed, Google Scholar, and Web of Science were searched from inception to September 30, 2022, and all comparative studies involving eESWL and dESWL for ureteral calculi were included. Statistical analysis was performed using Review Manager 5.3 software. Results A total of 9… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…In a meta-analysis that included 9 studies, SFR in upper ureteral stones was found to be 79.5% in early SWL and 63.4% in deferred SWL within 1 month follow-up. [6] In this study, the SFR within 1 month in the early SWL and deferred SWL groups were 85.5% and 71,8%, respectively. In both groups, the SFR was higher than that in the meta-analysis.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…In a meta-analysis that included 9 studies, SFR in upper ureteral stones was found to be 79.5% in early SWL and 63.4% in deferred SWL within 1 month follow-up. [6] In this study, the SFR within 1 month in the early SWL and deferred SWL groups were 85.5% and 71,8%, respectively. In both groups, the SFR was higher than that in the meta-analysis.…”
Section: Discussionmentioning
confidence: 46%
“…Some studies have reported that it is more successful if performed within the first 48 hours after the onset of colic pain. [5,6] The aim of this study aimed to determine the effectiveness of SWL performed in the early period, that is, within the first 24 hours, and to compare it with deferred SWL in terms of stone-free rates (SFR).…”
Section: Introductionmentioning
confidence: 99%